Outpatient pharmaceutical office: acceto medicines in public health - Morgado Junior, Belmiro; Abreu-Pereira, César Augusto [UNESP]; Ponce, Maria Amelia Zanon; Pagliuso, Rosana De Gasperi; Santos, Adriana Melo Jorge; Simone, Adriane Lopes Medeiros (FapUNIFESP (SciELO), 2023)
We evaluated the implementation of the outpatient pharmaceutical office in a teaching hospital regarding the access to medicines available in the Unified Health System – SUS. This is a descriptive-analytical study, based on secondary data analysis of 735 appointments performed by the pharmacist from 2015 to 2017. Of the drugs prescribed to patients attended at the outpatient pharmacist office, 86.39% were listed in the National List of Essential Medicines-RENAME, of which 95.43% belonged to the Specialized Component of Pharmaceutical Assistance. Evaluating the patient’s diagnosis against the inclusion criteria of the Clinical Protocols and Therapeutic Guidelines (PCDT), that the most frequent pharmaceutical interventions were: adequacy of the medication request documents (56.4%) and examination requests for pharmacotherapeutic follow up (28.5%). When the prescribed drugs were not included in RENAME/PCDT, the intervention was accepted in 90.3% of the proposals for exchange with available drug in SUS. Still, it was possible to refer the patient to primary care for renewal of continuity of treatment in 95.1% of cases. In conclusion, the role of the clinical pharmacist contributes to the resolution of untreated health problems by promoting access to medicines within the scope of SUS and their rational use in accordance with the PCDT.
Keywords: Access to essential medicines; Ambulatory care; Health policy; Pharmaceutical care; Unified health system